Musculoskeletal pains among amateur and professional athletes of five disciplines in Senegal: a preliminary study - Hassane Malam Moussa Ahmet; Elysée Claude Bika Lele; Wiliam Richard Guessogo; Wiliam Mbang Bian; Jessica Guyot; Ahmadou; Peguy Brice Assomo-Ndemba; Clarisse Noel Ayina; Loick Pradel Kojom Foko; Caroline Dupré; Nathalie Barth; Bienvenu Bongue; et al. (BMC Musculoskeletal Disorders, 2023)
Abstract Background Musculoskeletal pains (MSPs) in sport are cause of poor performances and loss of competition in athletes. The present study aimed at determining the prevalence of MSPs with regard to sport disciplines and athletic status. Methods A cross-sectional study was conducted among 320 Senegalese professional and amateur athletes practicing football, basketball, rugby, tennis, athletics, and wrestling. Rates of MSPs in the past year (MSPs-12) and week (MSPs-7d) were assessed using standard questionnaires. Results Overall proportions of MSPs-12 and MSPs-7d were 70 and 74.2%, respectively. MSPs-12 were more frequently reported on shoulders (40.6%), neck (37.1%) and hips/thigh (34.4%), while MSPs-7d were predominant on hips/thigh (29.5%), shoulders (25.7%), and upper back (17.2%). Proportions of MSPs-12 and MSPs-7d varied significantly by sport disciplines, with highest values among basketball players. Again, highest MSPs-12 proportions on shoulders (29.7%, P = 0.02), wrists/hands (34.6%, P = 0.001), (40.2%, P = 0.0002), and knees (38.8%, P = 0.002) were seen among basketball players. High proportions of MSPs-7d were seen on shoulders (29.6%, P = 0.04) for tennis players, wrists/hands (29.4%, P = 0.03) for basketball and football players, and hips/thigh (38.8%, P < 0.00001) for basketball players. Football players had reduced risk of MSPs-12 by 75% on lower back (OR = 0.25; 95% CI. 0.10—0.63; P = 0.003) and by 72% on knees (OR = 0.28; 95% CI. 0.08—0. 95; P = 0.04). In contrast, tennis players were more at risk of MSPs-12 on shoulders (OR = 3.14; 95% CI. 1.14–8.68; P = 0.02), wrists/hands (OR = 5.18; 95% CI.1.40–11.13; P = 0.01), and hips/thigh (OR = 2.90; 95% CI. 1.1–8.38; P = 0.04). Professionals were protected from MSPs-12 on neck pain with a significant reduction of risk by 61% (OR = 0.39, 95% CI. 0.21–0.75, P = 0.03). Conclusion MSPs are a reality among athletes and their risk is modulated by sport disciplines, athletic status and gender.